Unsoed Protani Inpago Rice Cultivation Field School at Ngudi Raharjo III Farmers Group, Lemberang Village: Sekolah Lapang Budidaya Padi Inpago Unsoed Protani Di Kelompok Tani Ngudi Raharjo III Desa Lemberang - Agus Riyanto; Rifki Andi Novia; Fatichin; Suwarto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The Ngudi Raharjo III Farmers Group, Lemberang Village, cultivates rice as the main commodity. This farmer group's rice field is located in the Siwuluh Block in Lemberang Village, Sokaraja District, Banyumas Regency. This rice field is located above a river flow, so it often experiences drought during the planting season. The problem in this farmer group is the limited availability of high-yielding and drought-tolerant lowland rice varieties. The solution to this problem is a field school for cultivating superior, drought-tolerant and high-yielding rice varieties resulting from the innovation of Jenderal Soedirman University, namely Inpago Unsoed Protani. Field school activities include counseling and Inpago Unsoed Protani rice cultivation demonstration plot. The results of this science and technology implementation activities are there has been a change in farmer behavior from tegel planting system to a jajar legowo system, Inpago Unsoed Protani has been successfully harvested and shows advantages that farmers like, and farmers are interested in planting Inpago Unsoed Protani in the next planting season.